Effect of basal metabolic rate on osteoporosis: A Mendelian randomization study - Zhou, Jingyu; Ye, Zhiwen; Wei, Peng; Yi, Feng; Ouyang, Min; Xiong, Shilang; Liu, Yayun; Li, Jintang; Liu, Min; Xi, Hanrui; Peng, Qianyi; Xiong, Long (Frontiers in Public Health, 2023)
Purpose: Basal metabolic rate may play a key role in the pathogenesis and progression of osteoporosis. We performed Mendelian random analysis to evaluate the causal relationship between basal metabolic rate and osteoporosis. Methods: Instrumental variables for the basal metabolic rate were selected. We used the inverse variance weighting approach as the main Mendelian random analysis method to estimate causal effects based on the summary-level data for osteoporosis from genome-wide association studies. Results: A potential causal association was observed between basal metabolic rate and risks of osteoporosis (odds ratio = 0.9923, 95% confidence interval: 0.9898–0.9949; P = 4.005e-09). The secondary MR also revealed that BMR was causally associated with osteoporosis (odds ratio = 0.9939, 95% confidence interval: 0.9911–0.9966; P = 1.038e-05). The accuracy and robustness of the findings were confirmed using sensitivity tests. Conclusion: Basal metabolic rate may play a causal role in the development of osteoporosis, although the underlying mechanisms require further investigation.